Phénomènes limites: un essai sur l’ambiguïté de la nature: Part 2: The Human in Nature - Jackson, Michael (Anthropologica, 2022)
ather than argue that nature is a collection of phenomena that are sui generis interrelated, this article explores the idea of nature as a manifestation of an existential frontier between what can and what cannot be apprehended, selected and controlled directly by human action or agency. Through ethnographic examples, personal reflections and theoretical digressions, this article reveals that the unstable thresholds between eigenwelt, mitwelt and umwelt are loci of ceaseless, ambivalent and unfortunate oscillations between ways of being passive and active and between life and death.